Pemberdayaan Kelompok Ikatan Guru TK Indonesia (IGTKI) dalam Mendukung Pemerolehan Komunikasi Bahasa Inggris Anak Usia Dini Berbasis Aplikasi Digital - Nurbaiti Ali; Heni Wulandari; Rizky Vita Losi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This Community Service Program aims to enhance the knowledge and skills of kindergarten teachers through social and managerial aspects in partnership with the Indonesian Kindergarten Teachers Association (IGTKI) in Medan Deli District. The program involved nearly 50 kindergarten teachers from various schools in the district. The method used for this community service is Participatory Action Research (PAR), which consists of five stages: to Know, to Understand, to Plan, to Act, and to Change. The first stage aims to identify the conditions and needs of the kindergarten teachers, followed by a deeper understanding of the importance of early childhood English communication. The participants were then involved in planning and taking action through training on the use of digital applications and creating flipbook e-modules to support early childhood English teaching. Evaluation of the activities was conducted using pre-test and post-test instruments via Google Form, showing a significant improvement of 70-90 from the total score of 100. Additionally, 80% of participants committed to continuously using digital applications and flipbook e-modules in their schools. Overall, this community service activity successfully provided significant benefits in enhancing the knowledge and skills of IGTKI partners in Medan Deli, particularly in supporting the development of early childhood English communication skills.